Serum lipid, homocysteine, and platelet derived growth factor in patients with hypertension - Patcharaporn Aree (2019)
© 2019, Patcharaporn Aree, Tanyarat Jomgeow, Krid Thongbunjob and Chiraporn Tachaudomdach. Purpose: The purpose of this paper is to study serum lipids, lipoproteins, homocysteine (Hcy) and platelet-derived growth factor (PDGF), and to evaluate the relationship between serum lipids, lipoproteins, Hcy and PDGF in patients with hypertension. Design/methodology/approach: In total, 85 patients with hypertension (34 males, 51 females) were recruited from October to December 2015 at Saraphi Hospital, Chiang Mai Province using purposive sampling. PDGF mRNA levels of the patients were analyzed using the RT-PCR method. Hcy was analyzed by high-performance liquid chromatography. An enzymatic-colorimetric method was used to measure serum cholesterol, high-density lipoprotein cholesterol and triglyceride. A low-density lipoprotein cholesterol (LDL-C) level was calculated using Friedewald’s formula. Descriptive statistics and the Pearson product moment were also used in the analysis. Findings: Among the patients with hypertension, hypercholesterolemia, high levels of LDL-C, hypertriglyceridemia and hyperhomocysteinemia were found in 54.1, 70.7, 25.9 and 44.7 percent, respectively. In addition, PDGF was significantly correlated with Hcy (r=0.705; p<0.005). There was no association between serum lipids or lipoproteins and Hcy or PDGF in patients with hypertension. Practical implications: The results of this study provide direction on how serum lipids, lipoproteins, Hcy and PDGF can be used as a guide to improving dietary management as a means of reducing cardiovascular disease, and stroke in patients with hypertension. Originality/value: This manuscript is not currently under consideration, in press or published elsewhere. This manuscript is truthful original work without fabrication, fraud or plagiarism. The authors have made important scientific contributions to this study. The authors are familiar with the primary data, and have read the entire manuscript and take responsibility for it content. No benefits were received by the authors or any member of the authors’ family or the research team, from any commercial source, directly or indirectly related to this work. Moreover, no one affiliated with has any financial interest related to the subject matter of this manuscript.